BIOESSAY TO TEST THE PATHOGENICITY OF Beauveria bassiana (Bals.) Vuill. ON THE COFFEE BERRY BORER Hypothenemus hampei (Ferrari) - GONZÁLEZ-G., MARÍA TERESA; POSADA-F., FRANCISCO J.; BUSTILLO-P., ALEX E. (Revista Colombiana de Entomología, 1993)
The coffee berry borer Hipothenemus hampei (Ferrari) is the most serious insect pest of the coffee plantations. Among the biological control methods the fungus Beauveria bassiana (Bals.) Vuill. may play an important role in borer population reduction. In this research, a bioassay method was standardized to test the pathogenicity of B. bassiana on H. hampel. Adults of the borer were obtained from a laboratory mass rearing using parchment coffee at 45% R.H. The borers were disinfected with sodium hypochlorite at 0,5% for 10 minutes and rinsing the excess in three washes with sterile distilled water. The experiment was organized in a complete randomized design using three treatments formed by isolate Cenicafe Bb-9205 from Diatraea saccharalis (Bb-9205 DS), the same isolate passed through the borer (Bb9205 BFC) and a control. Thirty adults of the borer were used per replication. These insects were exposed to the fungus using a concentration of 1 x 107 conidia/ml for two minutes and then transferred individually in glass vials (4 ccs of capacity) with a piece of wet paper inside and capped with absorbent cotton. Twenty-four hours later a berry of waxed-parchment coffee with 45% of humidity was added as a substrate. Infected insects showed reduced activity, loss of legs and antennae, and therefore inability to bore the coffee grain. Treated insects with the fungus resulted in lower grain attack (14.44%) compared with control insects (44.44%). There were significant differences (130.05) among treatments, average mortality was 88.88% for isolate Bb-9205 DS and 100% for Bb-9205 BFC. Mean lethal time (TL50) was 92.4 hours with isolate Bb-9205 DS and 54.72 hours with Bb-9205 BFC. Five stages of development of B. bassiana on H. hampei were recognized: inoculation to death, death to initial mycelial growth, death to mycelial c3verage, death to conidiogenesis, and death to discharge of conidia. These stages lasted 20.16; 31.92; 56.40; 83.28 and 198 hours for Bb-9205 DS and 20.88; 44.40: 66.88; 116 and 182 hours for Bb-920r BFC. This bioassay can be used as a model to evaluate different entomopathogens to be tested against H. hampei.